The Dynamics of Land Ownership Within the Framework of Agrarian Regulation Asynchrony and its Implications for Land Conflicts and Social Injustice in Indonesia - Agusra Yendri; Megawati Barthos (Ridwan Institute, 2026)
Land ownership and agrarian governance in Indonesia remain complex due to historical legacies, regulatory fragmentation, and sectoral law conflicts, resulting in recurrent land disputes and social inequities. Despite constitutional mandates emphasizing state control and the social function of land, inconsistencies between the Basic Agrarian Law (UUPA) and various sectoral regulations create legal uncertainty, overlapping authority, and unequal land distribution. This study aims to analyze the dynamics of land ownership within the framework of asynchronous agrarian regulations and to propose a harmonized model for sustainable and socially just land governance. The research employed a normative juridical approach, combining legislative and conceptual analyses of relevant laws, regulations, and academic literature. Data are collected from constitutional provisions, statutory laws, sectoral regulations, and scholarly studies, followed by thematic coding and content analysis to identify regulatory gaps, conflicts, and socio-legal implications. Triangulation ensures validity, and repeated document verification maintains reliability. Findings indicate that regulatory disharmony has contributed to structural inequality, marginalization of communities, and recurrent land conflicts, highlighting gaps in legal synchronization and enforcement of social functions of land. The study’s novelty lies in integrating vertical and horizontal regulatory analyses with prescriptive recommendations for agrarian policy reconstruction, providing a comprehensive framework to achieve legal certainty, equitable land distribution, and social justice. This research offers a theoretical and practical contribution to agrarian legal reform in Indonesia.